Abatement costs of emissions from burning maize straw in major maize regions of China: Balancing food security with the environment. (20th January 2019) - Hou, Lingling; Keske, Catherine; Hoag, Dana; Balezentis, Tomas; Wang, Xiaobing
Abstract: This paper estimates the shadow price of CO2 from burning maize straw in the Chinese agricultural sector and explores the related policy implications for decision makers. Using a quadratic directional distance function, we evaluate the production inefficiency and shadow prices of CO2 reduction for the seven major maize-producing provinces in China for 1996–2014. In general, the efficiency improves over time. Shandong province ranked as the top one with full efficiency considering both economic and environmental impacts as of 2014. The mean shadow price for the CO2 emission was 0.45 yuan/kg (US75/t), whereas the province-specific shadow prices varied within the interval bounded by 0 and 0.913 yuan/ha (US152/t). The marginal abatement cost curve was downward-sloped and indicated the need for curbing CO2 emission in areas exhibiting the highest pollution rates. Given the marginal abatement cost patterns, the transaction costs associated with implementation of the conservation practices (tillage) should not exceed 335 yuan/ha in order to ensure the welfare gains. This government-provided payment would compensate farmers for yield reductions in favor of implementing conservation practices that would substantially reduce CO2 emissions.